Answer:
D. Rx) = x2 - 4x + 10
Step-by-step explanation:
R(x)=(x-2)^2+6
R(x)=(x-2)^2+6
=(x-2)(x-2)+6
=x^2-2x-2x+4+6
=x^2-4x+10
R(x) = x^2 - 4x + 10
Option D is the answer
18x^5-3x^4+x^3-x^2-72x^3+12x^2-4x+4, and then you will combine like terms to be :
18x^5-3x^4-71x^3+11x^2-4x+4
Answer:
A-1
Step-by-step explanation:
It perfectly represents the scenario.
No because there are two of the same inputs(x) (2,5) and (2,7)
Answer:
lbs or pounds
Step-by-step explanation:
but usually pounds are a unit of weight and not mass